Resource accounting, sustainable development and well-being - Karl-Göran Mäler (Fondazione Eni Enrico Mattei (FEEM), 1997)
There are now quite many publications on the construction of an environmentally adjusted net-national product measure. Most of these publications base the discussion on rather ad hoc constructions of the national accounts. In this paper, I try to develop an accounting framework from basic economic principles and relate this framework to the notion of sustainable development. I then review a few empirical studies in view of the findings of this paper. In an appendix, the discussion in the main text is supported by mathematical analysis.
Keywords: 330; Umweltökonomische Gesamtrechnung; Nachhaltige Entwicklung; Sozialrechnungsmatrix; Theorie